SIKAP GENERASI MUDA TERHADAP BAHASA INDONESIA - Suhita, Raheni (Jurnal Inovasi Pendidikan, 2011)
The objectives of the research is to know: (1) The knowledge and the confidence of the young generation on Indonesian language; (2) The valuation to the young generation on Indonesian language; (3) The inclination of the young generation to take measures in using Indonesia language; (4) The exist and unexist of the influence of gender variable, the education level and the education level and the back ground of mother language on the attitudes of young generation to Indonesian language. The sample research is 300 young generation, consist of 60 students of SMK, 120 students of SMU, 120 the university students from government and private universities. Which was taken by multiplestage cluster random sampling techniques. Based on the data analysis descriptively, it can be concluded: (1) The young generation have positive confidences on Indonesian language; (2) The young generation have positive valuation on Indonesian language; (3) The young generation have an inclination to take positive measures by using Indonesian language. While from the result of the data analysis by using T-examination technique, it can be concluded: (1) There is a gender influence on the language attitudes from the young generation; (2) There is an influence of the education level on the language attitudes from the young generation; (3) There is an influence on the back ground of mother language on the young generation attitude.